Rainwater toxicity and contamination study from So Paulo Metropolitan Region, Brazil - Martins, Renata S. L.; Abessa, Denis M. S. [UNESP]; Fornaro, Adalgiza; Borrely, Sueli I. (Springer, 2014)
Wet deposition is an important process that removes pollutants from the atmosphere and transfers them to waters and soil. The goal of this study was to assess the biological effects of the atmospheric contamination of rainwater in the metropolitan area of So Paulo (MASP) using Daphnia similis, Ceriodaphnia dubia, and Vibrio fischeri. Experimental assays were carried out according to standard toxicity methodology. Twenty-three rainwater samples were collected from October 2007 to December 2008, at the Nuclear Research Institute (IPEN), in MASP. Major ions were determined by ionic chromatography, which showed NH4 (+) and NO3 (-) as prevalent ions. Ecotoxicological results confirmed toxic potential of rainwater, as all samples were toxic to D. similis and C. dubia. The V. fischeri luminescence reduction confirmed those negative effects of rainwater and percentage inhibition of relative luminescence ranged from 0.2 to 0.9 for 16 samples. Worse conditions were observed during the rainy season, suggesting convective rains are more effective in transferring contaminants and toxicity from atmosphere to surface.
Keywords: Air pollution; Urban area; Rainwater; Toxicity; Wet deposition